Bim Execution Process of Construction Companies for Building Projects - İlal, Mustafa Emre; Gercek, B.; Günaydın, Hüsnü Murat; Tokdemir, O.B.; Ilal, M.E.; Gunaydin (ISEC Press, 2017)
Building Information Modeling (BIM) has been an emerging concept in architecture, engineering and construction (AEC) industry with a vast amount of promising benefits to construction projects. Implementation of BIM, however, requires comprehensive research and strategic planning. Industry-wide and organizational implementation guidelines and standards have been published around the world either to encourage organizations to adopt BIM or to present the minimum requirements to be followed where BIM implementation is a statutory obligation. In contrast, governments or organizations in several countries such as Turkey have not mandated BIM implementation and provide no guidance. Organizations in these countries which plan to adopt BIM processes are forced to develop their own implementation plans. The purpose of this study is to provide guidance in BIM implementation for construction companies in countries where BIM implementation has not been mandated particularly during the construction phase of the building projects. 23 BIM standards and guidelines covering the BIM execution process have been reviewed. Topics that need to be addressed by BIM implementation plans have been identified and categorized under four headings. A case study of BIM implementation at a large construction company that focuses on conducting quantity takeoff and cost estimation is presented, and unique challenges of BIM implementation in Turkish AEC industry are discussed. © 2017 ISEC Press.
Keywords: BIM guidelines; BIM implementation; BIM standards; Construction management; Execution plan; Implementation guidelines